Poland - Improving the Financial Sustainability of the Hospital Sector : Towards a Systemic Approach - World Bank (Washington, DC, 2014)
Over the past twenty years, the Polish health system has undergone several deep systemic changes. Poland spends more of its healthcare budget on inpatient hospital care than comparable countries, signaling an area of inefficiency that requires reform ahead of demographic trends. Ownership of public hospital facilities is fragmented between different levels of government, leading to multiple stakeholders and a lack of accountability. Poland has made significant progress in rationalizing its hospital system and reducing the number of beds, but the reform agenda remains unfinished as evidenced by the continuing debt issue. This note outlines a path to improving the financial sustainability of the hospital sector in Poland. The anatomy of the debt problem is examined and major obstacles to financial health are systematically reviewed. The root causes of barriers are analyzed from a managerial as well as a health system perspective, including the role of regulatory and financing constraints. In making the case for change, the report also discusses how secular trends, for instance in population health and service delivery, need to be taken into account as plans to reshape the hospital system are being formulated. Preliminary recommendations are made distinguishing: (i) system-level changes which will require national-level policy interventions, and (ii) options for Voivodships and facility managers to work better within the existing system and enhance the chances of selecting no regret move investments.